Multiple XEN Gel Stents for Refractory Pediatric Glaucoma - Ruparelia, Sunil; Berco, Efraim; Lichtinger, Alejandro; Shoham-Hazon, Nir (Journal of pediatric ophthalmology and strabismus, 2022)
Although trabeculotomy and goniotomy are currently the mainstay of surgical management for congenital glaucoma, XEN Gel Stent (Allergan) implantation and other microinvasive glaucoma surgery technologies may offer the advantage of having a lower risk of postoperative complications than conventional techniques. A 10-year-old boy presented with aphakic glaucoma in his left eye secondary to previous cataract surgery. Intraocular pressure (IOP) in the left eye at initial presentation was 31 mm Hg with maximal tolerated medical therapy. Surgical history included tube shunt, shunt revision, and subsequent shunt removal. Shunt surgery and revision had been unsuccessful at achieving target IOP. The patient underwent two treatments of micro-pulse transscleral laser therapy that failed to achieve target IOP. At this time, an open conjunctiva ab externo superior XEN Gel Stent (Allergan) was implanted. Within 1 month of surgery, conjunctival dehiscence and contraction occurred. Following this, ab interno inferonasal air–ophthalmic viscosurgical device XEN Gel Stent implantation was performed. In the 6 months following the second XEN Gel Stent, IOP in the left eye was stable at 6 to 8 mm Hg. This report describes the effective use of a XEN Gel Stent implant in the management of congenital glaucoma, while also highlighting a complication. Further studies are required to determine the comparative outcomes of this technique with conventional surgical management. [J Pediatr Ophthalmol Strabismus. 2022;59(1):e11–e14.]